IMPLEMENTASI PROGRAM TAHFIDZ AL-QUR’AN JUZ 30 (STUDI MULTISITUS DI MTS N 1 DAN MTS N 3 LAHAT SUMATERA SELATAN) - Hidayat, Ahmad Zaki; Rahmat, Rahmat; Usman, Fadly (Raudhah - Proud To Be Professional, 2025)
In line with the development of the times, MTsN 1 Lahat and MTsN 3 Lahat have implemented the tahfidz program of juz 30. This tahfidz program of juz 30 is a superior program adopted by the Ministry of Religion as a form of habituation for students to memorize the Al-Qur'an, especially for juz 30. This program must be followed by all students from grade VII to grade IX. The target to be achieved is to make graduates of this junior high school as memorizers of the Al-Qur'an juz 30. The objectives of this study are, 1) To analyze the implementation of the tahfidz program of Al-Qur'an juz 30 at MTs N 1 Lahat and MTs N 3 Lahat. 2) To analyze the supporting and inhibiting factors in the implementation of the tahfidz program of Al-Qur'an juz 30 at MTsN 1 Lahat and MTsN 3 Lahat. Meanwhile, the type of research used in this study is a qualitative research type in the form of a multi-site study approach at MTs N 1 Lahat and MTs N 3 Lahat. The results of this study are, first, in the implementation of memorizing the Al-Quran juz 30 which is held every Friday at MTs N 1 Lahat, the talaqqi method is applied. This method includes various other approaches such as the bi nazhar method which involves looking at the mushaf, as well as tahfidz which focuses on memorization. After students memorize, they will submit their memorization to the instructor with a maximum limit of 5 verses. Second, the Implementation of the Al-Qur'an Juz 30 Memorization Program with the Muraja'ah Method and Supporting and Inhibiting Factors at MTs N 3 Lahat. By carrying out memorization and deposit every day, as well as doing tashih every week to repeat memorization and assess the extent of reading fluency, tahfidz becomes very effective.